Immunity of children to diphtheria, tetanus, and poliomyelitis. Issue 6167 (31st March 1979) - Bainton, D; Freeman, M; Magrath, D I; Sheffield, F; Smith, J W
Abstract : A survey of titres of diphtheria and tetanus antitoxins and of antibodies to polioviruses in the sera of 291 schoolchildren aged 15, 11, and 7 years showed that high immunisation rates can evoke protective concentrations of tetanus antitoxin in 98% of children and protective levels of the antibodies to diphtheria and all three types of poliomyelitis in 85% of children. Reinforcing immunisation at school entry appeared to be necessary to maintain adequate titres of diphtheria antitoxin in children up to 15 years of age, not essential to maintain adequate titres of tetanus antitoxin, and to have little effect on the titres of antibodies to poliomyelitis.